Electrochemical Response of Saccharomyces cerevisiae Corresponds to Cell Viability upon Exposure to Dioclea reflexa Seed Extracts and Antifungal Drugs - Arthur, P.K.; Yeboah, A.B.; Issah, I.; Balapangu, S.; Kwofie, S.K.; Asimeng, B.O.; Foster, E.J.; Tiburu, E.K. (Biosensors, 2019)
Dioclea reflexa bioactive compounds have been shown to contain antioxidant properties. The extracts from the same plant are used in traditional medical practices to treat various diseases with impressive outcomes. In this study, ionic mobility in Saccharomyces cerevisiae cells in the presence of D. reflexa seed extracts was monitored using electrochemical detection methods to link cell death to ionic imbalance. Cells treated with ethanol, methanol, and water extracts were studied using cyclic voltammetry and cell counting to correlate electrochemical behavior and cell viability, respectively. The results were compared with cells treated with pore-forming Amphotericin b (Amp b), as well as Fluconazole (Flu) and the antimicrobial drug Rifampicin (Rif). The D. reflexa seed water extract (SWE) revealed higher anodic peak current with 58% cell death. Seed methanol extract (SME) and seed ethanol extract (SEE) recorded 31% and 22% cell death, respectively. Among the three control drugs, Flu revealed the highest cell death of about 64%, whereas Amp b and Rif exhibited cell deaths of 35% and 16%, respectively, after 8 h of cell growth. It was observed that similar to SWE, there was an increase in the anodic peak current in the presence of different concentrations of Amp b, which also correlated with enhanced cell death. It was concluded from this observation that Amp b and SWE might follow similar mechanisms to inhibit cell growth. Thus, the individual bioactive compounds from the water extracts of D. reflexa seeds could further be purified and tested to validate their potential therapeutic application. The strategy to link electrochemical behavior to biochemical responses could be a simple, fast, and robust screening technique for new drug targets and to understand the mechanism of action of such drugs against disease models.
Keywords: Electrochemical detection; Dioclea reﬂexa; Bioactive; Amphotericin; Rifampicin; Cell viability